1982
DOI: 10.1038/bjc.1982.84
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of T-lymphocyte subsets in Hodgkin's disease characterized by monoclonal antibodies

Abstract: Summary.-Mononuclear-cell suspensions of lymph nodes, spleen and blood from 24 patients with active Hodgkin's disease (HD) were studied for possible imbalance of T and B lymphocytes, and T-lymphocyte subsets, using monospecific anti-T antibodies and other reagents. A profile showing T-cell predominance was demonstrated ln lymph nodes and blood, with total T-cells ranging from 50-70% of the cell count. As defined by monoclonal antibodies, 70-85% of the latter comprised the "inducer" subclass, the remainder bein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

1983
1983
1997
1997

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 28 publications
2
9
0
Order By: Relevance
“…Morris & Stuart (1984) found that CD4+ T-cells attached more frequently to RS/HM cells than CD8 + T-cells in fresh cell suspensions prepared from Hodgkin's involved lymph nodes. Previous studies have shown that for the majority of HD cases of all subtypes studied, with the exception of the lymphocyte depleted subtype, the majority of the T-cell population in the involved node are of the CD4+ subset (Dorreen et al, 1982;Poppema et al, 1982;Abdulaziz et al, 1984) and thus, the apparently more frequent association of CD4 + T-cells with RS/HM cells may simply reflect the higher proportion of CD4+ cells available to compete for attachment.…”
Section: Discussionmentioning
confidence: 92%
“…Morris & Stuart (1984) found that CD4+ T-cells attached more frequently to RS/HM cells than CD8 + T-cells in fresh cell suspensions prepared from Hodgkin's involved lymph nodes. Previous studies have shown that for the majority of HD cases of all subtypes studied, with the exception of the lymphocyte depleted subtype, the majority of the T-cell population in the involved node are of the CD4+ subset (Dorreen et al, 1982;Poppema et al, 1982;Abdulaziz et al, 1984) and thus, the apparently more frequent association of CD4 + T-cells with RS/HM cells may simply reflect the higher proportion of CD4+ cells available to compete for attachment.…”
Section: Discussionmentioning
confidence: 92%
“…Even T lymphoblastic lymphomas show some evidence of being composed of mixtures of phenotypically distinct subsets of cells, which may mimic the normal patterns of phenotypic variation occurring during intrathymic differentiation. The T cell component in Hodgkin's Disease (Dorreen et al, 1982) or in follicular lymphoma is often not demonstrably abnormal in respect of the relative proportions of T "helper" or "suppressor" cells, or in their distribution as assessed by frozen section. Nonetheless, mixtures of such cells do, in individual patients, show the capacity for progressive growth, ultimately with the emergence of a dominant B cell population showing light chain class restriction, and probably derived from a single B cell clone.…”
Section: Phenotypic Heterogeneity In Peripheral Tcellsmentioning
confidence: 99%
“…For 28K29 and 28B49 (a negative control) cells, HT was further added to the serumfree medium. (Dorreen et al, 1982). Then, the wells were washed three times with PBS containing 0.05% Tween 20 (Tween 20/PBS) and blocked with PBS containing 3% BSA.…”
Section: Lymphocytesmentioning
confidence: 99%